KESEJAHTERAAN PETANI PELAKU USAHATANI POLIKULTUR TERINTEGRASI DI KABUPATEN TASIKMALAYA - Nuryati, Rina; Sulistyowati, Lies; Setiawan, Iwan; Noor, Trisna Insan (Universitas Galuh Ciamis, 2019)
Indonesia has the potential for extensive dry land (LK). These FIs are generally in critical status and are located in disadvantaged villages, most of which are managed by poor farmers who are unable to carry out conservation efforts, so that their conditions deteriorate. The pattern of agricultural development in accordance with the characteristics of FIs is integrated farming. Integrated farming has three main functions, namely improving welfare and encouraging economic growth, food security and maintaining environmental sustainability. The well-being of the farm family is the output of the resource management process and overcoming the problems faced by the farmer family. The study aims to determine the welfare of farmers who are UTPPT actors. Research method: survey of 250 farmers in Tasikmalaya Regency in a proportional random sampling manner. Data were analyzed by analysis of income structure and expenditure structure / consumption of farmer RT food, as well as the exchange rate of rural household income (NTPRP). The results of the study: the income of farmer households comes from the agricultural and non-agricultural sectors as well as from the income of family members. Revenues from the agricultural sector are obtained from polyculture farming (forestry, plantation, horticulture and food) and livestock business. The contribution of livestock business income is greater (37.99%) than polyculture farming (35.52%) and non-agricultural (26.49%) and family member income (7.91%). Income from UTPPT is the biggest contributor to farmer household income. A total of 71.46% of farmer families share the income from the agricultural sector> 80%. As many as 63.67% of farmers depend entirely on the agricultural sector. The share of food expenditure for farmer households is still quite high, 42.19% of farmer households spend between 60-80% and> 80% on food. NTPRP has a value of> 1, farmers experience a surplus which includes the category of prosperity.